Piercing the corporate veil from the angle of case law - Секулић, Александра С. (Zbornik radova Pravnog fakulteta u Novom Sadu, 2024)
Piercing the corporate veil represents one of the most contraversal institutes in company law because it represents a deviation from the rules on limited liability. As this institute became part of the judicial practice, the judicial practice is very important in the analysis of the given institute. There are some comparative legal systems in which this institute is often applied in judicial practice. On the other hand, there are systems, including domestic ones, in which this institute is rarely and cautiously applied in practice. The main goal of the research in this paper is the analysis of the institute of piercing the corporate veil and its significance in Company law, with a special reference to domestic judicial practice and the analysis of certain characteristics of comparative judicial practice.